2001
DOI: 10.1093/hmg/10.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Methylation profiles of DXPas34 during the onset of X-inactivation

Abstract: X chromosome inactivation is controlled by the cis-acting X-inactivation centre (Xic). In addition to initiating inactivation, Xic, which includes the XIST: gene, is involved in both a counting process that senses the number of X chromosomes and the choice of X chromosome to inactivate. Controlling elements lying 3' to XIST: include the DXPas34 locus. Deletion of DXPas34 in undifferentiated embryonic stem (ES) cells eliminates expression of both XIST: and the antisense transcript TSIX:, thought to initiate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…Interestingly, imprinted regulation of Ascl2 operates in a methylation-independent manner (Caspary et al, 1998;Tanaka et al, 1999). The Xist gene and its antisense transcript, Tsix, also lack germline-derived methylation imprints (McDonald et al, 1998;Prissette et al, 2001). This suggests either that imprinting is disrupted through different mechanisms for distinct genes or that a uniform process upstream of methylation operates at all imprinted loci, resulting in disruptions to both imprinted gene expression and methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, imprinted regulation of Ascl2 operates in a methylation-independent manner (Caspary et al, 1998;Tanaka et al, 1999). The Xist gene and its antisense transcript, Tsix, also lack germline-derived methylation imprints (McDonald et al, 1998;Prissette et al, 2001). This suggests either that imprinting is disrupted through different mechanisms for distinct genes or that a uniform process upstream of methylation operates at all imprinted loci, resulting in disruptions to both imprinted gene expression and methylation.…”
Section: Discussionmentioning
confidence: 99%
“…Lee proposed the presence of an imprinting center within the CpG-rich domain overlapping the Tsix promoter which responds to activating maternal and repressive paternal signaling to facilitate imprinted Tsix expression (17). Analysis of the DXPas34 locus and the Tsix promoter by bisulfite sequencing revealed that methylation does not represent the imprinting mark and is also unlikely to play a role in the regulation of Tsix transcription from this site (35). However, it cannot be excluded that the imprinting is associated with a methylation-independent mechanism.…”
mentioning
confidence: 99%
“…2A), a possibility congruent with the imprinted status of the Xs in extraembryonic cells in which the stereotypical paternal X silencing is the rule. Although the field has yet to reach a consensus on the nature of the "imprint," differential CpG methylation within the Xist-Tsix-Xite regions has been implicated (Norris et al 1994;Ariel et al 1995;Courtier et al 1995;Zuccotti and Monk 1995;McDonald et al 1998;Prissette et al 2001;Boumil et al 2006). We note that slight differences in the methylation pattern and the lack of functional evidence thus far leave open the question of which, if any, of these marks constitute the primary imprint.…”
Section: X-chromosome Inactivation: Two Identical Substrates Two Oppmentioning
confidence: 83%